Horses for courses? Assessing the potential value of a surrogate, point‐of‐care test for SARS‐CoV‐2 epidemic control. Issue 1 (6th August 2020) - Ismail, Sharif A.; Huntley, Catherine; Post, Nathan; Rigby, Samuel; Shrotri, Madhumita; Williams, Sarah V.; Peacock, Sharon J.
Abstract: Point‐of‐care tests (POCTs) offer considerable potential for improving clinical and public health management of COVID‐19 by providing timely information to guide decision‐making, but data on real‐world performance are in short supply. Besides SARS‐CoV‐2‐specific tests, there is growing interest in the role of surrogate (non‐specific) tests such as FebriDx, a biochemical POCT which can be used to distinguish viral from bacterial infection in patients with influenza‐like illnesses. This short report assesses what is currently known about FebriDx performance across settings and populations by comparison with some of the more intensively evaluated SARS‐CoV‐2‐specific POCTs. While FebriDx shows some potential in supporting triage for early‐stage infection in acute care settings, this is dependent on SARS‐CoV‐2 being the most likely cause for influenza‐like illnesses, with reduction in discriminatory power when COVID‐19 case numbers are low, and when co‐circulating viral respiratory infections become more prevalent during the autumn and winter. Too little is currently known about its performance in primary care and the community to support use in these contexts, and further evaluation is needed. Reliable SARS CoV2‐specific POCTs—when they become available—are likely to rapidly overtake surrogates as the preferred option given the greater specificity they provide.